2021
DOI: 10.3390/s21206745
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Optimized Preprocessing and Modeling Algorithms for Prediction of Soil Properties Using VIS-NIR Spectroscopy

Abstract: The absorbance spectra for air-dried and ground soil samples from Ontario, Canada were collected in the visible and near-infrared (VIS-NIR) region from 343 to 2200 nm. The study examined thirteen combination of six preprocessing (1st derivative, 2nd derivative, Savitzky-Golay, Gap, SNV and Detrend) method included in ‘prospectr’ R package along with four modeling approaches: partial least square regression (PLSR), cubist, random forest (RF), and extreme learning machine (ELM) for prediction of the soil organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Apart from the difference in costs of the used instruments and the level of portability, there was no obvious benefit of vis-NIR system over mid-IR, or vice versa. The stated error estimates reported in this study and in earlier studies ( Table 1 ) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 39 , 40 ] are higher than those corresponding to traditional analysis, where the laboratory method has a detection limit of 20 g kg −1 for sand and clay (dry basis), and generally, is reproducible to within ±80 g kg −1 , Ref. [ 49 ].…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Apart from the difference in costs of the used instruments and the level of portability, there was no obvious benefit of vis-NIR system over mid-IR, or vice versa. The stated error estimates reported in this study and in earlier studies ( Table 1 ) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 39 , 40 ] are higher than those corresponding to traditional analysis, where the laboratory method has a detection limit of 20 g kg −1 for sand and clay (dry basis), and generally, is reproducible to within ±80 g kg −1 , Ref. [ 49 ].…”
Section: Resultssupporting
confidence: 67%
“…These portable instruments are built using semiconductor technologies and they are relatively inexpensive, robust, and simpler to use when compared to laboratory-based bench-top instruments. They are suitable for deployment in the field for proximal sensing [ 1 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Numerous studies support their use for the simultaneous assessment of primary and secondary soil properties on the go [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In many previous studies, predictive models of SOM, carbon, and nitrogen were developed using the PLSR model, which extracted complex absorption patterns and demonstrated high levels of efficiency when investigating a correlation between patterns and soil [ 17 , 19 , 20 , 21 , 22 ]. Owing to the relationship between spectral data and soil characteristics rarely being linear, studies applying neural networks and machine learning-based ANN, SVR, and random forest have been conducted [ 5 , 23 , 24 ]. Although Vis-NIR spectroscopy is considered a well-established method for estimating soil properties, no accepted universal model currently exists that is widely applied [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Visible and near infrared reflectance (Vis-NIR) spectroscopy has been widely used to rapidly analyze many properties in various types of soils or sediments [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. As the primary chemical attribute, organic carbon in soils or sediments (SOC) is directly related with Vis-NIR reflectance and has been mainly investigated for 20 years [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies also showed that ASD spectrometers are the most commonly used in the Vis-NIR spectral analysis due to their good performance and reputation [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 17 , 18 , 19 ]. However, ASD spectrometers are expensive, being a barrier to studies on Vis-NIR spectroscopy [ 13 , 18 ].…”
Section: Introductionmentioning
confidence: 99%